Adsorption Of Copper(Ii ) And Nickel(Ii) Ions Onto Chemically Treated Candlenut Shell - Yeoh, Kim Hoey (2016)
The candlcnut shell from food industry was treated with different types of chemicals to evaluate their potential and performance adsorbents in the removal of Cu2+ and Ni2+ metal ions in aqueous solution. Treated candlenut shell (TCS) adsorbents were subjected to COD. TOC, pHZpc- FTIR. SEM-EDX.